Isoproterenol mechanisms in inducing myocardial fibrosis and its application as an experimental model for the evaluation of therapeutic potential of phytochemicals and pharmaceuticals - Lujain Bader Eddin; Mohamed Fizur Nagoor Meeran; Niraj Kumar Jha; Samer N. Goyal; Shreesh Ojha (Animal Models and Experimental Medicine)
Abstract Cardiac injury initiates repair mechanisms and results in cardiac remodeling and fibrosis, which appears to be a leading cause of cardiovascular diseases. Cardiac fibrosis is characterized by the accumulation of extracellular matrix proteins, mainly collagen in the cardiac interstitium. Many experimental studies have demonstrated that fibrotic injury in the heart is reversible; therefore, it is vital to understand different molecular mechanisms that are involved in the initiation, progression, and resolution of cardiac fibrosis to enable the development of antifibrotic agents. Of the many experimental models, one of the recent models that has gained renewed interest is isoproterenol (ISP)–induced cardiac fibrosis. ISP is a synthetic catecholamine, sympathomimetic, and nonselective β‐adrenergic receptor agonist. The overstimulated and sustained activation of β‐adrenergic receptors has been reported to induce biochemical and physiological alterations and ultimately result in cardiac remodeling. ISP has been used for decades to induce acute myocardial infarction. However, the use of low doses and chronic administration of ISP have been shown to induce cardiac fibrosis; this practice has increased in recent years. Intraperitoneal or subcutaneous ISP has been widely used in preclinical studies to induce cardiac remodeling manifested by fibrosis and hypertrophy. The induced oxidative stress with subsequent perturbations in cellular signaling cascades through triggering the release of free radicals is considered the initiating mechanism of myocardial fibrosis. ISP is consistently used to induce fibrosis in laboratory animals and in cardiomyocytes isolated from animals. In recent years, numerous phytochemicals and synthetic molecules have been evaluated in ISP‐induced cardiac fibrosis. The present review exclusively provides a comprehensive summary of the pathological biochemical, histological, and molecular mechanisms of ISP in inducing cardiac fibrosis and hypertrophy. It also summarizes the application of this experimental model in the therapeutic evaluation of natural as well as synthetic compounds to demonstrate their potential in mitigating myocardial fibrosis and hypertrophy.